MENGUATKAN INDONESIA: REVITALISASI PEMBELAJARAN PENDIDIKAN KARAKTER - Cahyadi, Ani (Universitas Islam Negeri Raden Intan Lampung, 2014)
REVITALIZATION OF CHARACTER EDUCATION LEARNING: This article discusses some of the issues related to character education in Indonesia, ranging from the concepts and Islamic values related to character education to learning patterns that will be applied. This work concludes that Pancasila which becomes the core values in the formation of the Indonesian nation-state can be used as a reference in preparing the character education learning program and it, by no mean, conflicts withIslamic values. By using elaborative-analysis approach, this study offers a number of initial concepts that can be used to revitalize Pancasila and Religious Education through a multi- dimensional-based framework.